Pola Kalimat Tunggal Murid Tk Di Kecamatan Namlea Kabupaten Buru: Analisis Trasformasi Generatif - Taufik, Taufik; Amir, Nur Fadhilah Amir (Lembaga Layanan Pendidikan Tinggi Wilayah XII, 2020)
Children's language has unique patterns or rules. This study aims to analyze the single sentence patterns of kindergarten students in Namlea District with the Tatabahasa Transformasi Generative (TTG) by Noam Chomsky. The results showed that there were two structural patterns of phrases in the language of kindergarten students, namely FN + FV and FN + FA. Furthermore, the form of single sentence kindergarten students can be seen from two types of transformation, namely negative and passive transformation. These two types of transformation have a physical and mental structure. The two structures produce different transformation patterns. For negative transformation, the birth structure has a pattern of K —-> Neg + FN [Su] + FV + FN [Ob]. This pattern will change when transformed negatively into K —-> Neg + FN [Su] + FV + FN [Ob].Furthermore, the structures born in the passive transformation have a pattern of K —-> FN [Su] + FV + FN [Ob]. This pattern will change when transformed passively into K —-> FN + FN [Su] + FV. Based on the results of this study, it can be concluded that the language of kindergarten children in Namlea District has a pattern in accordance with the development of the language.